El sermón como forma de comunicación y como estrategia de movilización Nuevo Reino de Granada a principios del siglo XVII - Silva, Renán (Sociedad y Economía, 2001)
The political situation in 17th Century Hispanic colonial societies has been little studied and is very often poorly understood. One possible reason for this situation is related to a lack of understanding of the nexus between the prevailing political situation and the theology of the church, as expressed by its colonial clergy. This essay presents a first attempt at comprehending aspects of the prevailing theological disputes and the resulting confrontations between the religious orders within the Catholic Church. Central to the struggle was the dogma of the immaculate conception. The manner in which the general populous and the notables were involved in these competing theological influences had an important influence on the politics of colonial America.